Zagadnienie lichwy w ujęciu wielkich religii monoteistycznych - Ramocka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2008)
This article provides a comparative analysis of the attitudes of three major monotheistic religions – Judaism, Christianity and Islam – to the practice of usury and looks at why these attitudes developed in different ways. Each of the parts presents the opinions of one of the religious systems, analysing the Old and New Testaments, as well as the Koran, by looking at the duties that the Holy Scriptures required of their followers. The first part is devoted to Judaism. According to this model, the moral value of usury was dependent on the ethnic and religious origins of the borrower probably because of special historical and cultural associations between the idea of money and the Jewish people. The second part is concerned with usury in Christian religion, presenting the attitude expressed in the Gospel, as well as later comments of Fathers of the Church, in order to put the change in moral attitudes to usury in its historical context. Finally, the article presents the point of view of Islam devoting particular attention to the historical reasons for the development of its specific attitude to usury, but also outlining contemporary solutions adopted in the present-day Islamic world.